X-ray Chest in Congenital Diaphragmatic Hernia: A Case Report - Millsep Sieroka; Firstia Anugerah Rerung Allo; Aditya Oktavianto; Sharon Griselda Tedjo; Erica Valencia Imannuel; Richard Gunawan; Fiky Cahyarania Insyara; Ingrid Yesty Giovanni Hutasoit; Suci Sapira Koirunisa; Mathias (Rumah Sakit Unggul Karsa Medika, 2023)
Congenital diaphragmatic hernia (CDH) is characterized by the presence of pulmonary hypoplasia or agenesis involving the left, right or both lungs, the failure of diaphragmatic closure, and the herniation of abdominal organs into the thoracic cavity. The incidence of diaphragmatic hernia ranges from approximately 0.8-5/10,000 births and varies across populations. The signs and symptoms including respiratory distress and bowel sounds in the chest cavity, no breathing sounds in one of the hemithorax and shifting of heart sounds. Chest X-ray is simple yet mostly available modality to confirm the diagnosis.